Letter to Jane Tolmach from Eugene V. Kennedy - Eugene V. Kennedy:::::: (1963)
Eugene V. Kennedy informs Mrs. Jane Tolmach that she has been appointed to the Democratic State Central Committee. He explains that the Committee will meet at the State Capitol on Sunday, August 11, at 10:00 a.m., the day after the State Convention. Kennedy notes that she may attend either in person or by proxy. If she cannot attend, she must complete and return the enclosed proxy form to the Secretary of State's office by 5:00 p.m. on Saturday, August 10.